2016
DOI: 10.1021/acs.jpcc.6b03529
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Phase and Optical Properties of Ultrathin SnSx Films

Abstract: Novel materials suitable for optoelectronics are of great interest due to limited and diminishing energy resources and the movement toward a green earth. We report a simple film growth method to tune the S composition, x from 1 to 2 in semiconductor ultrathin SnS x films on quartz substrates, that is, single phase SnS, single phase SnS2, and mixed phases of both SnS and SnS2 by varying the sulfurization temperature from 150 to 500 °C. Due to the ultrathin nature of the SnS x films, their structural and optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 75 publications
7
30
0
Order By: Relevance
“…The decay time and density of trap states of the films sulphurised at 300 and 350 o C were tabulated in Table 1. Our first decay time value in SnS phase is comparable to the previous reports [4,5] 3.0x10 -6 3.5x10 -6 4.0x10 -6 4.5x10 -6 5.0x10 -6 5.5x10 -6 6.0x10 -6 6.5x10 -6 7.0x10 …”
Section: Persistent Photoconductivitysupporting
confidence: 90%
See 1 more Smart Citation
“…The decay time and density of trap states of the films sulphurised at 300 and 350 o C were tabulated in Table 1. Our first decay time value in SnS phase is comparable to the previous reports [4,5] 3.0x10 -6 3.5x10 -6 4.0x10 -6 4.5x10 -6 5.0x10 -6 5.5x10 -6 6.0x10 -6 6.5x10 -6 7.0x10 …”
Section: Persistent Photoconductivitysupporting
confidence: 90%
“…The E g increased from 1.70 to 2.45 eV with the increase of sulphurisation temperature from 300 to 500 o C, respectively. The band gap (Eg) values of 1.38 eV for SnS phase and of 2.21 eV for SnS2 phase were recently reported [4]. The difference in Eg values was mainly due to the difference in the deposition techniques employed and process parameters maintained during the growth of the films.…”
Section: Structural Propertiesmentioning
confidence: 92%
“…For all three typical films, only one Raman peak located around 220 cm -1 was presented in Figure 4. This Raman peak was attributed to LO phonon mode of SnS phase [6]. Regarding to the peak intensity, it suggested that the films prepared at source temperature of 600 o C revealed the best crystal quality due to the strongest peak intensity.…”
Section: Ror Structural Analysismentioning
confidence: 90%
“…One commonly known technique is the deposition of a thin tin layer with subsequent sulfurization at high-vacuum conditions, as reported by Yang and coworkers for the fabrication of SnS x films. 13 Miles et al directly evaporated pure SnS powder and obtained a smooth tin-sulfide layer with a thickness of a few micrometers on glass substrates. 14 Depending on the substrate temperature, additional phases of SnS 2 or Sn 2 S 3 appeared.…”
Section: Introductionmentioning
confidence: 99%